2022
DOI: 10.1007/s12671-022-01992-7
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Mindfulness App on Postnatal Distress

Abstract: Objectives The present study investigated the effectiveness of an 8-week mindfulness mobile phone app on women’s depression, anxiety, stress and mindful attention/awareness in the postnatal period. Methods The study enrolled 99 mothers of a child under 1 year old, and randomly assigned them to intervention (n = 49, mean age = 31.11, SD = 4.30, years) and control (n = 50, mean age = 31.35, SD = 5.29, years) groups. Multiple regression examined intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…For the 12 RCTs, the assessment periods ranged from a few months up to two years. Interestingly, some studies with a larger sample size had relatively shorter study periods compared to those with a smaller sample size [24] [29] . The duration of the interventions also varied, with most studies conducting assessments at three time points [24] , [27] , [30] [32] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the 12 RCTs, the assessment periods ranged from a few months up to two years. Interestingly, some studies with a larger sample size had relatively shorter study periods compared to those with a smaller sample size [24] [29] . The duration of the interventions also varied, with most studies conducting assessments at three time points [24] , [27] , [30] [32] .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, some studies with a larger sample size had relatively shorter study periods compared to those with a smaller sample size [24] [29] . The duration of the interventions also varied, with most studies conducting assessments at three time points [24] , [27] , [30] [32] . The remaining studies conducted assessments twice [26] , [29] , [33] , [34] , four times [28] , and up to five times [23] , [25] between the baseline and the end of the study period.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these structural, societal, and individual barriers, internet-based interventions (IBIs) have emerged as a recognized and easily accessible means of providing specialized therapeutic care to women with the potential to both prevent and treat postpartum depressive symptoms [ 19 21 ]. IBIs targeting PPD commonly use evidence-based treatment elements, such as CBT techniques including behavioral activation and cognitive restructuring [ 22 24 ], psychoeducational components [ 24 – 26 ], and mindfulness and self-compassion practices [ 24 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…These digital interventions can increase accessibility, as the tracks can be played at any time, and allow the standardisation of the intervention with a highly skilled individual directing participants through the mindful practises (Mrazek et al, 2019). Several studies have confirmed the effectiveness of audio mindfulness in the improvement of subjective wellbeing (e.g., Bear et al, 2022;Keng et al, 2022); however, significant within-group differences in perceived stress and difficulties in sustaining engagement are often reported (Huberty et al, 2019).…”
mentioning
confidence: 99%